A case study of the language policy in practice in the foundation phase of schooling - Brookes, Margaret Ann (Rhodes University, Faculty of Education, Department of Education, 2002)
This interpretative case study takes place in the foundation phase of a previously parallel medium school in the Eastern Cape. Learners from all three major language groups of the province (English, Xhosa and Afrikaans) are enrolled at the school. The study examines the language attitudes of teachers, parents and young learners and records their language practices in the classroom, the wider school environment and at home. Research carried out through this case study found that all stakeholders perceive English as the language of access to improved education and lifestyle. All young learners displayed a positive attitude to multilingualism and were keen to be able to speak all three provincial languages. The attitudes of their parents and teachers however differed from the learners and each other. The teachers and the English speaking parents were primarily concerned with the maintenance of the standards of English. The Afrikaans and Xhosa speaking parents were committed to their children developing proficient English language skills even if this meant supporting the development of their primary language and culture at home. Furthermore it was discovered that little attention had been paid to developing a school language policy in accordance with the new Language in Education Policy of July 1997. This policy promotes an additive approach to bilingualism and seeks to ensure that meaningful access to learning is provided for all children. By suggesting steps that could be taken by this school to develop their own language policy, the study highlights the necessity of recognising and remedying the gaps between policy and practice in the issue of language rights, identity and education in general.
Keywords: Language policy -- South Africa; English language -- Study and teaching (Elementary) -- South Africa